(S)-N1,N3-Dibenzyl-1-cyclohexyl-N1,N3-bis((R)-1-phenylethyl)propane-1,3-diamine - Leland Belda; Ángel García-González; Alejandro Manchado; Carlos T. Nieto; Narciso M. Garrido (Molbank, 2023)
(S)-N1,N3-dibenzyl-1-cyclohexyl-N1,N3-bis((R)-1-phenylethyl)propane-1,3-diamine was prepared in good yield by the reduction of the corresponding amide, which was obtained by the addition of a chiral lithium amide to an α,β-unsaturated ester. The target compound was fully characterized by NMR (1H and 13C), high-resolution mass spectrometry and polarimetry.